Automatic Fire Alarm Extinguisher - Mohamad Shahran, Afiq Faris; Mohd Zaki, Muhammad Asyraf (2016)
The project title Automatic Fire Alarm Extinguisher is a project which consist of the temperature sensor, smoke sensor, buzzer, LED, GSM SIM900, water pump and others. Roughly this project consist of two part that are fire alarm system and the GSM system that sent the message to owner. For the information this project use two sensor that is temperature sensor and the smoke sensor. The PIC16F877A was used to make the connection complete. This system has their advantage and disadvantage. The advantage of this system is to make the people more alert to the fire and can take the action quickly. This also make easy to the owner to know that his house in fire. So, he can take some quick action by save the important document or call the fire department. However, this also help when there nobody at house while the house is getting to a fire. The water pump will be on as the extinguisher to extinguish the fire. One of the disadvantages of this project it needed power source to work. If the user’s house is running out of electricity or having a total blackout, this project will come to no use. Next, this project needed some precise and specific components to make it run. Any kind of unneeded components will make it not functioning as it supposed to be.